2012
DOI: 10.5433/1679-0359.2012v33n1p333
|View full text |Cite
|
Sign up to set email alerts
|

Intereference of storage temperatures in the development of mesophilic, psychrotrophic, lipolytic and proteolytic microbiota of raw milk

Abstract: With the objective of comparing distinct storage conditions of raw milk, 20 samples of raw milk were collected, and portions of each were stored at different storage conditions (4°C for 48 h, 7°C for 48 h and 25°C for 4 h). Populations of mesophilic aerobes and psychrotrophics (total, lipolytic and proteolytic) were monitored, and the results were compared by analysis of variance (ANOVA, P < 0.05). Psychrotrophics were randomly selected and identified. Mesophilic aerobes had significant development after 48 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 8 publications
3
16
1
5
Order By: Relevance
“…De acordo com os produtores, essa permanência elevada ocorria, pois tra tavamse de propriedades com peque na pro dução, de menor relevância para o atendimento da indústria de processamento, ca racterizando-se como prática visando con tenção de custo por parte do laticínio. A ne gligência ao atendimento dos padrões de tempo e temperatura compromete o controle da multiplicação de microrganismos no leite, uma vez que quanto maior o tempo de armazenamento do leite sem processamento, mais rápida será a deterioração dos seus derivados (HARYANI-ANWAR et al, 2003;PERIN et al, 2012).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…De acordo com os produtores, essa permanência elevada ocorria, pois tra tavamse de propriedades com peque na pro dução, de menor relevância para o atendimento da indústria de processamento, ca racterizando-se como prática visando con tenção de custo por parte do laticínio. A ne gligência ao atendimento dos padrões de tempo e temperatura compromete o controle da multiplicação de microrganismos no leite, uma vez que quanto maior o tempo de armazenamento do leite sem processamento, mais rápida será a deterioração dos seus derivados (HARYANI-ANWAR et al, 2003;PERIN et al, 2012).…”
Section: Resultsunclassified
“…Esta contagem costuma apresentar correlação positiva com a contagem de bactérias psi crotróficas (CBP) no produto, outra im por tan te ferramenta no monitoramento da qualidade do leite. Microrganismos psicro tróficos fre quentemente produzem enzimas proteolí ti cas e lipolíticas associadas à alterações tec no lógicas e sensoriais no produto mesmo após processamento, devido à capacidade de termorresistência destas enzimas (OLIVEIRA et al, 2000;CHEN et al, 2003;PERIN et al, 2012).…”
Section: Introductionunclassified
“…Segundo Perin et al (2012), quando a contagem inicial de mesófilos aeróbios no leite cru é maior que 100.000 UFC/mL o desenvolvimento da microbiota psicrotrófica é significativamente maior do que em um leite com contagem inicial baixa.…”
Section: Introductionunclassified
“…Yamazi et al (2013) also reported low protein contents and decreased yield in cheese from raw goat milk kept refrigerated for more than 48 hours. According to Perin et al (2012), when raw milk is stored at 4°C, for an extended time period, the dairy product yield is reduced due to the growth of proteolytic psychrotrophic bacteria within 48 hours. As over 80% of the psychrotrophic microorganisms in raw milk may determine proteolysis, the remaining proteolytic activity must be considered even when milk is pasteurized or subjected to ultra-high temperature treatment prior to yogurt production (Nörnberg et al, 2010).…”
Section: Physicochemical and Microbiological Characteristicsmentioning
confidence: 99%